CULTURE OF LANGUAGE AS A PART OF CULTURE VOCATIONAL AND COMMUNICATION WORKERS LEGAL LEGAL FIELD - Барановська, Л. В.; Циганій, С. О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
This paper analyzes the aspects of language culture understanding. The significance of linguistic accuracy, linguistic variation and linguistic skills has been revealed to effectively perform professional functions of legal sector workers. The role of a lawyer’s speech culture in the judicial and nonjudicial forms of professional activity has been concretized